Simulation and modeling methodologies, technologies and applications : International Conference, SIMULTECH 2014 Vienna, Austria, August 28-30, 2014, revised selected papers /: International Conference, SIMULTECH 2014 Vienna, Austria, August 28-30, 2014, revised selected papers. ([2015]) - Unknown
No abstract available